2021
DOI: 10.1111/trf.16410
|View full text |Cite
|
Sign up to set email alerts
|

Assessing predictors of futility in patients receiving massive transfusions

Abstract: Background: Massive transfusions are associated with a high mortality rate, but there is little evidence indicating when such efforts are futile. The purpose of this study was to identify clinical variables that could be used as futility indicators in massively transfused patients. Methods: We retrospectively analyzed 138 adult surgical patients at our institution receiving a massive transfusion (2016)(2017)(2018)(2019). Peak lactate and nadir pH within 24 h of massive transfusion initiation, along with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 36 publications
1
32
1
Order By: Relevance
“…There are few studies examining blood transfusion volume as an indicator for futility in trauma patients receiving MT and UMT. 7,26,28,32,38,39 Dzik et al’s 26 multicenter retrospective study of 1360 trauma, surgical, and medical patients who received UMT demonstrated that although transfusion volume was associated with an increase in mortality, it was the underlying diagnosis category that was more strongly associated with mortality. The trauma patient subgroup had the lowest survival rates of all the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies examining blood transfusion volume as an indicator for futility in trauma patients receiving MT and UMT. 7,26,28,32,38,39 Dzik et al’s 26 multicenter retrospective study of 1360 trauma, surgical, and medical patients who received UMT demonstrated that although transfusion volume was associated with an increase in mortality, it was the underlying diagnosis category that was more strongly associated with mortality. The trauma patient subgroup had the lowest survival rates of all the patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,[15][16][17][18][19] Trauma patients may receive extremely high quantities of blood products during uncontrolled hemorrhagic shock; however, survival is not guaranteed, and it reduces the availability of this precious resource for patients with survivable injuries, thus jeopardizing their care and outcomes. 7 A serious ongoing issue is a national blood shortage due to decreased blood donations and cancelation of blood drives resulting in 86,000 fewer blood donations in 2020. 19,20 Furthermore, there is a significant cost associated with blood products.…”
Section: Glossarymentioning
confidence: 99%
“…In patients with non‐survivable injuries or bleeding not amenable to surgical intervention, transfusion medicine physicians and other hospital representatives have been forced to intervene in dire inventory scenarios, but otherwise continue to provide products. In hospitals considering futility protocols, it has been shown that profound acidosis (pH <7.00), elevated lactate (≥10 mmol/L) and advanced age (≥ 65 years) were associated with increased mortality for patients undergoing massive transfusion; 32 however, there were many outliers in that analysis which prevented a reliable predictive algorithm from being developed, and thus it remains impossible to reliably predict mortality even amongst the massively transfused. As evidenced by our respondents, futility protocols are generally felt to require a group consensus and would optimally include an institution's clinical ethicist as well as other stakeholders who may form a transfusion triage team 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Acidosis and hyperlactataemia are frequently used markers of organ hypoperfusion and critical illness; as such, they have been studied as potential predictors of mortality, with a nadir pH less than 7.0 and peak lactate of 10 mM or more associated with higher mortality in massively transfused patients. 20 A study on trauma patients with massive haemorrhage that aimed to determine utility of initial arterial pH as a prognostic indicator showed that the average pH value was lower in non-survivors, and a single value of <6.9 was associated with 90% mortality. 21 Overall evidence indicates that severe acidosis carries an increased risk of mortality; however, as no threshold for pH predicts 100% mortality, this alone cannot be used as a futility marker.…”
Section: Limited Evidence For Predictors Of Futility In Acutely Criti...mentioning
confidence: 99%